Hu Paper (Chinese Talisman) as A Medium Healing - Hartati, Celerina Dewi (Tradition and Modernity of Humanity, 2021)
Amulet paper in Chinese culture is known as hu / fu 符paper. It can serve as a means of healing. This amulet paper can mean healing because it is changed from something ordinary or profane to sacred through a ceremony performed by a spirit medium (tangsin). When God enters the body of the spirit medium through trance, the spirit medium performs a ritual such as slash the tongue. With the spirit medium's blood, he wrote this amulet paper. The paper then has a sacred function as medicine. This research is an ethnographic study with a case study at Hok Lay Kiong Bekasi temple during the Capgomeh ceremony and the God's birthday ceremony. The hu paper has so far been better known as a means of obtaining good fortune and luck. Through this paper, we can see Hian Thian Siang Tee’s amulet paper at Hok Lay Kiong Temple as a medium healing in Chinese society and see the changing function from something profane to sacred thing.